Ancient place-names in the governorate of Kafr el-Sheikh - Engsheden, Åke, 1969- (Orientalia Lovaniensia Analecta ;, 2021)
This book is a diachronically oriented toponomastic study of a single northern Egyptian governorate. At its core it is a gazetteer of ancient place names that are likely to have, or have been claimed to have, origins either in ancient Egyptian, Coptic, or Greek. It provides an extensive list of attestations, collected from diverse sources that range from Predynastic hieroglyphic labels to modern town signs. Despite the focus on ancient toponyms, its point of departure is current non-Arabic place-names in modern Egypt because so much documentation from antiquity is lacking. The book also includes results from onomastic fieldwork that was conducted in the area with the aim of ascertaining local pronunciations and folk etymologies. It highlights the high density of ancient names still present in a region that is under-represented in ancient texts, and thus offers a new perspective on the development of the northern fringes of the Delta. The study should be of interest to Egyptologists, Arabists, and anyone concerned with the origins and development of place names.0.